Cryptic diversity of Leurus wasps (Hymenoptera: Ichneumonidae: Metopiinae), parasitoids of caterpillars in Area de Conservación Guanacaste, Costa Rica - Zuñiga, Ronald; Valerio, Alejandro A.; Hanson, Paul; Smith, M. Alex; Hallwachs, Winnie; Janzen, Daniel H. (Zootaxa, 2024)
As a consequence of COI barcoding hundreds of reared specimens of what appeared to be Leurus caeruliventris, a parasitoid of leaf-rolling Crambidae (Lepidoptera) from the Area de Conservación Guanacaste, northwestern Costa Rica, and matching them with their host caterpillars and morphological traits, we describe ten new sympatric species and redescribe L. caeruliventris. The new species, authored by Zuñiga & Valerio, are: Leurus billeberhardi, L. henrytownesi, L. hugokonsi, L. iangauldi, L. jesusugaldei, L. marjorietownesae, L. maryjanewestae, L. pammitchellae, L. sondrawardae, and L. wahli. We also provide an illustrated key to the eleven species and an ecological glimpse into the lives of these very similar wasp species.